Lundbeck v. Commission: the first decision of the European General Court on reverse payments - Athanasiadou, Amalia (My University, 2016)
On September 8, 2016, the General Court of the European Union published its decision on Lundbeck v. Commission, its first decision on patent settlements involving reverse payments. This commentary focuses on the main points of the Lundbeck decision: the role of the patent and of the presumption of patent validity in the antitrust analysis, the issue of potential competition and the importance of the size of the payments. It presents the General Court’s analysis and considerations which led to a finding of a restriction of competition by object and also discusses the influence of the U.S. Supreme Court’s decision in FTC v. Actavis on the General Court’s reasoning. Finally, it argues that the General Court’s decision does not amount to a class condemnation of all patent settlements involving reverse payments as restrictions by object and maintains that the standard set by the Lundbeck decision is not necessarily harsher than the one embraced by FTC v. Actavis.
Keywords: Lundbeck v. Commission; reverse payments; pay for delay; patent settlements; pharmaceuticals; European competition law; Article 101 TFEU; restriction by object; intellectual property; antitrust; FTC v. Actavis